Significance of collateral circulation in managing persistent sciatic artery: Two case reports - Yun, Woo-Sung; Kim, Hyeon Ju; Hwang, Deokbi; Kim, Hyung-Kee (Frontiers in Surgery, 2023)
The treatment of persistent sciatic artery (PSA) should be based on patient symptom and PSA classification. Historically, the most common class has been known as type 2a in Pillet–Gauffre classification, and the mainstay of these patients with limb ischemia has been surgical bypass alongside excision or ligation of PSA aneurysm, if present. However, the current PSA classification system does not account for collateral blood flow, and in certain patients with sufficient collaterals, PSA with limb ischemia is treated with a minimally invasive method or conservative strategy. Herein, we described two cases of type 2a PSA and explored therapeutic choices for PSA based on collateral presence. Despite distal embolization in both patients, bypass surgery was avoided, and distal circulation was maintained via collaterals from deep and superficial femoral arteries without increased risk of recurrent embolization. Thus, the careful examination of computed tomography and customized strategy are important for managing PSA.